2021
DOI: 10.3390/cancers13102365
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Immune-Related Adverse Events, Glucocorticoid Use and Immunotherapy Interruption on Long-Term Survival Outcomes

Abstract: It remains unclear whether immune-related adverse events (irAEs) and glucocorticoid use could impact long-term outcomes in patients treated for solid tumors with immune checkpoint inhibitors (ICI). All patients treated with a single-agent ICI for any advanced cancer were included in this retrospective unicentric study. The objectives were to assess the impact of grade ≥3 irAEs, glucocorticoid use and the interruption of immunotherapy on progression-free survival (PFS) and overall survival (OS). In this 828-pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Several studies making comparisons within the group of patients with irAEs, demonstrate a detrimental effect of high dose corticosteroids on ICI efficacy, while no unfavourable effect was observed in other studies (Fig. 3 and Supplementary table 3 ) 13 , 41 , 46 , 47 , 56 66 . Most of the latter studies reported on small groups or low-dose corticosteroid use during ICI irrespective of indication, or included multiple types of cancer or ICI which have different survival and toxicity profiles and are often unequally distributed among groups.…”
Section: Corticosteroidsmentioning
confidence: 83%
“…Several studies making comparisons within the group of patients with irAEs, demonstrate a detrimental effect of high dose corticosteroids on ICI efficacy, while no unfavourable effect was observed in other studies (Fig. 3 and Supplementary table 3 ) 13 , 41 , 46 , 47 , 56 66 . Most of the latter studies reported on small groups or low-dose corticosteroid use during ICI irrespective of indication, or included multiple types of cancer or ICI which have different survival and toxicity profiles and are often unequally distributed among groups.…”
Section: Corticosteroidsmentioning
confidence: 83%
“…Some data suggests that early use of glucocorticoids (within 60 days of ICIs) may be associated with worse cancer outcomes, but further studies are needed to validate this finding. Recent data also suggests that this may also be due in part due to interruption or discontinuation of ICIs while patients have irAEs ( 8 ). Finally, glucocorticoids are used at varying dosages and durations depending on the type and severity of the irAE being treated.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Secondly, mixed reports are found regarding the effects of corticosteroids on survival when used for the treatment of irAE. While Mouri et al reported a negative effect from use of corticosteroids to treat irAE on both overall survival (OS) and progression free survival (PFS) (23) , Bruyère et al reported a negative effect on PFS, but not on OS (24) and multiple other studies reported that systemic corticosteroids for treatment of irAE do not reduce the survival effect of ICI (25)(26)(27)(28)(29)(30)(31)(32) . Thirdly, several studies showed that ICI are effective in autoimmune conditions, even when combined with systemic corticosteroids (33)(34)(35) .…”
Section: Introductionmentioning
confidence: 99%